Phytoplankton Community at Intensive Cultivation System of Whiteleg Shrimp, Litopenaeus vannamei in Probolinggo, East Java - Arifin, Nasrullah Bai; Fakhri, Muhammad; Yuniarti, Ating; Hariati, Anik Martinah (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2017)
Phytoplankton is a source of natural feed for shrimp cultivation in the pond. Phytoplankton productivity increases by the increasing nutrient content in the pond. Feed and metabolic waste is the sources of nutrient for phytoplankton growth. This study aimed to evaluate productivity and identify phytoplankton at intensive whiteleg shrimp, Litopenaeus vannamei cultivation system. This study was conducted at three intensive whiteleg shrimp located in Probolinggo, East Java. Samples were collected on the early and the late of culture period (day 17 and 87 after stocking). Four environmental parameters including total of ammonia nitrogen (TAN), nitrate, orthophosphate, total of suspended solid (TSS), and chlorophyll-a were measured. Identification and density of phytoplankton were also performed of each pond. The result showed that productivity of three ponds was 22,893.83 kg/ha to 23,600.61 kg/ha with an average size 12.74 g to 14.35 g. During culture period, the concentration of TAN, TSS and chlorophyll-a tended to increase. Meanwhile, the average of both nitrate and orthophosphate tended to decline. Several phytoplankton identified in this study were in the genus of Oocystis, Chlorella, Nannochloropsis, Chaetoceros, Stephanodiscus, Nitzschia, Coscinodiscus, Cyclotella and Ulothrix. Phytoplankton of the group Chlorophyta is predominance for pond 1 and 2, while pond 3 was dominated by phytoplankton in the group of Diatom/Baccillariophyta. This study indicated that the present of phytoplankton in the pond provide natural feed and good environmental condition for shrimp cultivation.